Prevalencia de pacientes con diabetes mellitus tipo 2 en tratamiento con hipoglucemiantes orales o insulina y la presencia de patologías tiroideas en el Hospital Manuel Ygnacio Monteros de Loja en el periodo 20102015 - Herrera Gonzalez, Johnny Fabian (2018)
Abstract:In Ecuador Diabetes Mellitus has a prevalence of 7.3%. It is estimated that 4.8% of Loja's population suffers from this pathology. It has been observed a relationship between diabetes mellitus type 2 and the development of thyroid pathologies in 10.8%, for which it is necessary to clarify this event. The objective of this investigation is to determine the prevalence of patients with diabetes mellitus type 2 treated with oral hypoglycemic agents, insulin and / or combinations thereof and who have developed thyroid pathologies at Hospital Manuel Ygnacio Monteros de Loja during the years 2010 to 2015. The present study is a quantitative, descriptive and transversal study in which all patients with Diabetes Mellitus Type 2, in treatment and who have developed thyroid pathology are included. It was found that 60.9% of patients with metformin, either as monotherapy or in combination with other oral hypoglycemic agents or insulin, have developed thyroid pathologies, especially hyporthroidism in 60.4% (n = 236). It concludes that there is a relationship between its use and the development of hypothyroidism, due to its probable participation in the reduction of thyroid stimulating hormone.